Considering dividend stability in the relation between dividend yields and stock returns - Ali, Syukriah (1996)
The main reason of this study is to examine the relationship between the dividend yields and stock returns by considering dividend stability. Besides that, this study also tends to examine the market value effect to the stock returns. Stocks that are qualified as a trustee stock listed on Kuala Lumpur Stock Exchange ( Industrial Product ) selected from July 1991 to June 1996 as a sample of the study. Samples of trustee stocks is considered because it's deem to have a stable dividend as long as it does not cut its dividends. Analysis is done through regression analysis and hypothesis testing. The best method for hypothesis testing is t-test. By comparing the result of t-value with tabular value we can determine whether there are significant relationship between dividend yield and market value to the stock returns. From the regression analysis conducted, it shows that dividend yield has higher positive relationship to the stocks returns as compared to the market value. According to the result of the t-test, it implies that there are significant relationship between dividend yield and stock returns. Also shown by the t-test, market value has no significant relationship to the stock returns. The significant relationship between dividend yield and stock returns exist because prices of stocks are much more depend on dividend payment. If dividend is high, therefore the price is also high thus the stocks tend to give the higher returns.